Frameless ROSA® Robot-Assisted Lead Implantation for Deep Brain Stimulation: Technique and Accuracy. Issue 1 (24th October 2019) - Liu, Lannie; Mariani, Sarah Giulia; De Schlichting, Emmanuel; Grand, Sylvie; Lefranc, Michel; Seigneuret, Eric; Chabardès, Stéphan
Abstract: BACKGROUND: Frameless robotic-assisted surgery is an innovative technique for deep brain stimulation (DBS) that has not been assessed in a large cohort of patients. OBJECTIVE: To evaluate accuracy of DBS lead placement using the ROSA® robot (Zimmer Biomet) and a frameless registration. METHODS: All patients undergoing DBS surgery in our institution between 2012 and 2016 were prospectively included in an open label single-center study. Accuracy was evaluated by measuring the radial error (RE) of the first stylet implanted on each side and the RE of the final lead position at the target level. RE was measured on intraoperative telemetric X-rays (group 1), on intraoperative O-Arm® (Medtronic) computed tomography (CT) scans (group 2), and on postoperative CT scans or magnetic resonance imaging (MRI) in both groups. RESULTS: Of 144 consecutive patients, 119 were eligible for final analysis (123 DBS; 186 stylets; 192 leads). In group 1 (76 patients), the mean RE of the stylet was 0.57 ± 0.02 mm, 0.72 ± 0.03 mm for DBS lead measured intraoperatively, and 0.88 ± 0.04 mm for DBS lead measured postoperatively on CT scans. In group 2 (43 patients), the mean RE of the stylet was 0.68 ± 0.05 mm, 0.75 ± 0.04 mm for DBS lead measured intraoperatively; 0.86 ± 0.05 mm and 1.10 ± 0.08 mm for lead measured postoperatively on CT scans and on MRI, respectively No statistical difference regarding the RE of the final lead position was found between the different intraoperative imaging modalities and postoperative CT scans in both groups. CONCLUSION: Frameless ROSA® robot-assisted technique for DBS reached submillimeter accuracy. Intraoperative CT scans appeared to be reliable and sufficient to evaluate the final lead position.